Od trnja do zvezd - odnosi z javnostmi v gozdarstvu - Lesnik, Anton (Gozdarski vestnik, 2014)
This article deals with basic concepts and terminology in the field of public relations, meaning of identity, mission, and values of the organization for communication with public, image of forestry in the public and roles of the media. In his article, the author states that the concept of 'public relations' is often narrowed only to the role of the media, but in reality it is much broader and complex. Many definitions for public relations are found in professional literature; the majority comprises the concepts of managing and communicating and public relations actually concern managed communication.On the basis of professional literature the author explains four basic models of communication with the public and emphasizes the best effectiveness of the two-way symmetrical model, since applying it, the organization communicates in such a way that it is also transformed in the process, i.e. it improves its work and eliminates its flaws. Building a strongidentity is also of utmost importance for the organization's communication with the public, although the identity does not always match with the public's perception, which is affected also by other factors, for example conflict of interests in public forestry service's activities. Organization's identity is also comprised in the text on the organization's mission and written values that have to be signed by all employees. The authorrealizes that only a minority of forestry organizations include the texton their mission in their presentation on the internet, while the written values are not noticeably presented. Regarding the forestry's image in the public, he finds that it is not objectively ascertained, however, we can find a low self-image, which is reflected also in the great request for positive presentation in the media which are not intended for promotion of organizations except in their payable advertising space. Positive image in the public can be established only performing the mission and reporting about it with quality. Thereby, proper and professional collaboration with media is very important.
Keywords: odnosi z javnostmi; forestry; gozdarstvo; communication; komuniciranje; identiteta; poslanstvo; vrednote